2012
DOI: 10.1016/j.ophtha.2012.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Intraocular Pressure after Cataract Extraction: The Ocular Hypertension Treatment Study

Abstract: Purpose To determine the change in intraocular pressure (IOP) after cataract extraction in the Observation Group of the Ocular Hypertension Treatment Study (OHTS). Design Comparative case series Participants Forty-two participants (63 eyes) who underwent cataract surgery in at least one eye during the study and a control group of 743 participants (743 eyes) who did not undergo cataract surgery Methods We defined the “split date” as the study visit date that cataract surgery was reported in the cataract s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
161
2
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(193 citation statements)
references
References 19 publications
14
161
2
16
Order By: Relevance
“…Since then, and particularly in the last decade, many studies have consistently shown a variable IOP decrease after cataract surgery (table 1) [5,6,7,8,9,10,11,12,13,14,15,16,17,18]. …”
Section: Ocular Biometric Parametersmentioning
confidence: 99%
“…Since then, and particularly in the last decade, many studies have consistently shown a variable IOP decrease after cataract surgery (table 1) [5,6,7,8,9,10,11,12,13,14,15,16,17,18]. …”
Section: Ocular Biometric Parametersmentioning
confidence: 99%
“…greater response seen in eyes with higher preoperative pressures. 15 For PACG eyes, the IOP response is much more and ranges from 2-8mmHg with a mean reduction of 6mmHg documented by a recent report released by American Academy of Ophthalmology (AAO). [16][17][18][19][20]10 Comparative studies between POAG and PACG subsets have clearly documented better response in ACG group in terms of IOP control and number of medications required, occurring despite a pre-existing patent laser iridotomy thus negating the aspect of relieving pupil block element as the sole cause.…”
Section: Effect Of Cataract Surgery On Intraocular Pressure Reductionmentioning
confidence: 99%
“…23 For those cases with poor control of pressure, IOP reduction after cataract surgery depends on height of pre-op values with a linear correlation irrespective of glaucomatous optic nerve changes. 5,9,15,25 Thus a decision to undertake a lens extraction alone needs to be individually tailored depending on target pressure, patient profile, adherence to medication and accessibility to medical care. Long term control of IOP is possible and two recent multicentre study groups (iStent study group and OHTS) have documented IOP reduction of 8.5 and 4mmHg post-phacoemulsification in the control arm over a follow up of 1-3 years.…”
Section: A Role In Open Angle Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1970s, Bigger and Becker reported a lower IOP after cataract extraction in glaucoma patients [7].…”
mentioning
confidence: 99%